Paying a visit: the Dalai Lama effect on international trade - Fuchs, Andreas; Klann, Nils-Hendrik (Journal of international economics, 2013)
Is political compliance a precondition for healthy trade relations with China? The Chinese government frequently threatens that meetings between its trading partners' officials and the Dalai Lama will be met with animosity and ultimately harm trade ties. We run a gravity model of exports to China from 159 partner countries between 1991 and 2008 to test the extent to which bilateral tensions affect trade with autocratic China. In particular, we empirically investigate whether countries that receive the Dalai Lama despite China's opposition experience a significant reduction in their exports to China. In order to account for the potential endogeneity of meetings with the Dalai Lama, the number of Tibet Support Groups and the travel pattern of the Tibetan leader are used as instruments. Our empirical results support the idea that countries officially receiving the Dalai Lama at the highest political level are punished through a reduction of their exports to China. However, this ‘Dalai Lama Effect’ is only observed for the Hu Jintao era and not for earlier periods. Furthermore, we find that this effect is mainly driven by reduced exports of machinery and transport equipment and that it disappears in the second year after a meeting took place.